38. Density Figure Of Aedes Spp Larvae In Jeulingke Village Syiah Kuala Subdistrict Banda Aceh - Farida Athailah; Muhammad Hanafiah; Eka Ichsan Prapanca; Lian Varis Riandi; Eliawardani Eliawardani; Muttaqien Muttaqien (Universitas Syiah Kuala, 2019)
This study was aimed to determine the level of Density Figure of Aedes spp mosquito larvae with parameter House Index (HI) Container Index (CI), and Breteau Index (BI) at Jeulingke Village, Syiah Kuala Subdistrict, Banda Aceh. This research was conducted by using Single Larva Method. Single Larvae Method is a method used to take a single larva by using a plastic scoop on each container that is found to have a larva and visually observed by using a flashlight. The sample used consisted of 120 houses taken randomly from 6 hamlets. The larval data were obtained from various types of containers tabulated into tabular form, then the larvae index was calculated to determine the density of the larvae based on the Density figure criteria. The results showed that from 120 houses found 702 containers in Jeulingke Village with 20 positive larval houses and 20 containers that positively contained larvae such as 19 bath containers and used tires by 1 container so that the index of larvae obtained with House Index is 17% , Container Index of 3%, Breteau Index 20, so as to obtain Density Figure value in the range of numbers 2-4. The results show that the Density Figure in Jeulingke Village is in the medium category.